ANALISIS PENGARUH TOTAL QUALITY MANAGEMENT TERHADAP KINERJA MANAJERIAL PADA PT. ARISAMANDIRI PRATAMA DI KOTA DEMAK - Widiastomo, Nugroho; Kusumawardhani, Amie (Diponegoro Journal of Management, 2015)
This study aims to examine the influence of Total Quality Management (TQM) toward managerial performance. With the increasingly widespread use of TQM in the business world, many companies grow rapidly and be able to compete in the market. According to Gaspersz, TQM is defined as a way of improving performance continuously (continuous performance improvement) at each level of operations or processes, in all functional areas of an organization with the use of all human and capital resources available.This study was conducted using a survey of middle-class manager at PT. Arisamandiri Pratama, a manufacturing company, and then analyzed using regression analysis. This study analyzed whether there was an effect on customer focus, obsession toward quality, teamwork, and employee involvement and empowerment on managerial performance.The results showed that the only variable which shows significant positive effect is the teamwork variable, while the other variables had no significant effect. In a manufacturing company, teamwork is the subject of work in order to ensure the company's production levels maintained, and even able to increase. With manager closeness to one another, their task can be solved immediately. While focusing on customers which actually gave negative effect rejected because PT. Arisamandiri Pratama’s most of the activities are just assembling the items ordered from other companies. They only get orders from other companies to manufacture goods. Therefore, the company may not pay much attention to customers and better kept focusing on production activities.